Sociabilidades mercantiles y prácticas comerciales de los mercaderes vascos en el Buenos Aires virreinal - Elsa Caula (Caravelle)
From a relational perspective and springing from information gotten form epistolary correspondence, this article studies the business practices of the Bask merchants who settled in Buenos Aires during the international war period towards the end of the eighteenth century. Having as observer Don Martin de Álzaga’s business house, we will explore the mechanisms that articulated the integrations of the business circuits of the River Plate area in the colonial economic system. Among them, the concrete deals carried out by the «bond agents» organized by the House’s boss within the familiar business constitution.